The Effect of Information Technology Perceptions and Complaint Handling on Customer Interests in Using BMM Mobile at PT. Bank Maluku Malut KC Ternate - Verawaty Verawaty; Faradiba Satasya Salsabila Effendi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This study aims to determine and analyze the influence of information technology perceptions and complaint handling on customer interest in using mobile BMM at PT Bank Maluku Malut KC Ternate. The method used in this study is multiple regression analysis using an instrument test consisting of a validity and reliability test, then the classical assumption test, namely the normality test, multicollinearity test, and heteroscedasticity test, and the hypothesis test, namely the t test and F test. The results of this study show that perceptions of information technology have a positive and significant effect on customer interest in using BMM Mobile at PT Bank Maluku Malut KC Ternate, and that handling complaints has a positive and significant effect on customer interest in using BMM Mobile at PT Bank Maluku Malut KC Ternate. And the results of the simultaneous test of information technology perceptions and complaint handling have a positive and significant effect on customer interest in using BMM Mobile at PT Bank Maluku Malut KC Ternate.